Patient satisfaction´s level with the nursing activities timetable. - Laura Carretero Cortes; Silvia Vicente Orgaz; Elena Sofía Palacios Arribas (Fundación para el Desarrollo de la Enfermería, 2011)
The assessment of patient satisfaction allows one the one hand to identify deficient areas from the point of view of the patient and on the other hand to evaluate the care outcomes.Patient´s opinion is an essential component in the assessment of the service. If patients are dissatisfied, care is far away from what it should be, no matter how high quality can be assesed through clinical indicators.The objective was to determine the patient satisfaction´s level with the schedule established in the hospital. Thus, a descriptive study that using simple random sampling the elements of the random sample were chosen directly in one step, assign each person hospitalized in a hospital in Toledo BZH a number and through a mechanical means (balls in a bag) we get random items that will be part of the sample (50 patients in the Hospital of Toledo BZH), so that each element in the population had an equal chance of being selected. The survey provides a closed, compilation, anonymous and voluntary.Results points to a certain degree of dissatisfaction among users, strict schedules and adapted to the "rotation" of health personnel, not patients.Analyzing the results in the development of activity schedules nursing activities: hygiene, feeding, etc ... we can see a big difference being a high percentage of patients who would prefer to change some schedules.